Dentists’ Knowledge and Management Strategies Towards Molar- Incisor-Hypomineralization in Tripoli - Najat Abushoufa (AlQalam Journal of Medical and Applied Sciences, 2024)
To assess the knowledge and clinical experience of dentists in Tripoli concerning MIH. Responses were gathered from Libyan dentists in Tripoli using both online and paper-based surveys. The survey tool collected information on participants’ sociodemographic details, clinical experience, perceptions, clinical management, and preferences for further training regarding MIH. The data was collected and analyzed using SPSS version 27. A total of 302 dentists had responded to the questionnaire, (62.6%) reported that they have come across MIH cases during their practice. Yellow/brown demarcations were reported as the most common presentation of MIH (49.7%). Most respondents reported that the best treatment options for treating MIH affected molars with post eruptive breakdown are pre-formed metal crowns (30.9%), followed by composite restorations (23.9%). The main barriers for treatment that were reported included child behavior (56.6%), and insufficient training to treat children with MIH (23.2%). This study showed awareness of the majority of participants of the existence of MIH condition. Nevertheless, variations in estimating MIH prevalence and its proper treatment, as well as factors influencing its treatment and diagnosis, were recorded. تقييم المعرفة والخبرة السريرية لأطباء الاسنان فى طرابلس حول نقص التمعدن فى القواطع والاضراس. تم استخدام طرق إدارة الاستبيانات عبر الإنترنت وعلى الورق لجمع الردود من أطباء الأسنان الليبيين في طرابلس. ركزت أداة الاستبيان على الخصائص الاجتماعية والديموغرافية للمشاركين ومعرفتهم وتصوراتهم حول أسباب نقص التمعدن فى القواطع والاضراس وكدلك طرق علاج هذه الظاهرة، والتصورات حول انتشار هده الظاهرة، وكيفية معالجتها، والتفضيلات للتدريب الإضافي. تم جمع البيانات وتحليلها باستخدام برنامج التحليل الاحصائى نوع 27. استجاب 302 طبيب اسنان للاستبيان حيت افاد62.6% منهم بانهم واجهو حالات نقص التمعدن فى الاضراس والقواطع خلال ممارستهم .تم الابلاغ عن العلامات الصفراء البنية كاكتر العروض شيوعا لنقص التمعدن فى الاضراس والقواطع بنسبة 49.7%. افاد معظم المستجيبين بان افضل خيارات العلاج للاضراس المتاترة بنقص التمعدن مع انهيار فى تاج السن بعد البزوغ هى التيجان المعدنية الجاهزة بنسبة 30.9%، تليها الترميمات المركبة بنسبة 23.9 % تم الابلاغ عن سلوك الطفل غير المتعاون 56.6% والتدريب غير الكافى لعلاج الاطفال المصابين بنقص التمعدن فى الاضراس والقواطع (23.2%) كأهم العوائق للعلاج. أظهرت هده الدراسة وعى غالبية المشاركين بوجود حالة نقص التمعدن فى الاضراس والقواطع, ومع ذلك تم تسجيل تباينات فى تقدير انتشار نقص التمعدن وعلاجه المناسب بالاضافة الى العوامل الموترة فى علاجه وتشخيصه .يوصى بمراجعة المنهج الدراسى الحالى لطب الاسنان وتوزيع الادلة العلمية التى توفر لأطباء الأسنان معلومات محدثة حول تشخيص وعلاج نقص التمعدن فى الاضراس والقواطع